2018
DOI: 10.2172/1484347
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Driven Steam Topping Cycle for a Binary Geothermal Power Plant

Abstract: Executive SummaryGreater deployment of moderate-temperature geothermal binary power plants (GBPPs) and concentrating solar power (CSP) can be limited in some markets by their respective generation characteristics and/or levelized cost of electricity (LCOE). Worldwide, both geothermal power and CSP are under intense pressure from the rapidly dropping cost of solar photovoltaic (PV) and wind energy. In the United States, there is further pressure from the ongoing era of low natural gas prices. CSP can generate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This LCOE value compares favorably with reported values for solar photovoltaic plus battery energy storage (PV+BES) systems in the open literature, i.e. $0.148/kWhe for a PV+BES system with 4 hours of electrochemical battery energy storage capacity (McTigue et al, 2018a;McTigue et al, 2018b). Addition of battery energy storage with more hours of storage would further increase PV+BES system LCOE and increase the separation between GeoTES and PV+BES.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…This LCOE value compares favorably with reported values for solar photovoltaic plus battery energy storage (PV+BES) systems in the open literature, i.e. $0.148/kWhe for a PV+BES system with 4 hours of electrochemical battery energy storage capacity (McTigue et al, 2018a;McTigue et al, 2018b). Addition of battery energy storage with more hours of storage would further increase PV+BES system LCOE and increase the separation between GeoTES and PV+BES.…”
supporting
confidence: 77%
“…4. The LCOE for high capacity GeoTES systems is lower than the value of $0.148/kWh estimated by McTigue et al (2018aMcTigue et al ( , 2018b for a low capacity (4 hr) photovoltaic plus battery energy storage (PV+BES) system. Addition of increased BES capacity would result in significant increases in PV+BES LCOE.…”
Section: Discussionmentioning
confidence: 76%
“…We have successfully completed all four tasks. The detail work regarding the tasks were summarized in the 68-page technical report [1]. In addition, one short article was published on the GRC bulletin [2] and one journal article [3] was just published on the high-impact journal: Applied Thermal Energy.…”
Section: Summary Of Research Resultsmentioning
confidence: 99%
“…The current study concentrates on the development of a new-build geothermal-solar or geothermalgas hybrid plant [11], as opposed to the previous projects which largely considered retrofitting an existing geothermal plant with solar thermal.…”
Section: Recap Of Previous Projectsmentioning
confidence: 99%
“…Previous work by this group, including McTigue et al's 2020 article [7], considered starting from a known geothermal plant and adding solar in the form of a steam Rankine topping cycle which feeds additional heat into an ORC-bottoming cycle. McTigue et al [19] studied the different possible options for moving heat from the solar thermal system to the geothermal cycle and found that using a topping cycle to add heat to the bottoming cycle working fluid provided the best compromise between efficiency and complexity. [7], [20], [21], [22].…”
Section: Literature Reviewmentioning
confidence: 99%